Mycobacterium mucogenicum from the Hickman line of an immunocompromised patient. Issue 1 (3rd August 2007) - Marshall, C; Samuel, J; Galloway, A; Pedler, S
Abstract : Gram stain of a positive blood culture is the clinician's first indication of a possible causative infective organism and a guide to suitable antimicrobial therapy prior to cultural and phenotypic identification with susceptibility test results. Occasionally interpretation of a Gram stain can be difficult; if there is a low bacterial load, no organisms may be seen. Such a case is reported, where a positive blood culture taken from the Hickman line of an immunocompromised patient flagged as positive at 5 days' incubation, but no organisms were seen on Gram film. On subculture, a slow growing Gram-positive bacillus was isolated which was initially misidentified and reported as a "diphtheroid" species. The actual identity of this organism and further isolates was later elucidated as Mycobacterium mucogenicum, a rapidly growing non-tuberculous mycobacterium.